DIFFICULTIES PERCEIVED BY WORKERS WITH DISABILITIES IN THE ROUTINE OF THEIR WORK - Chrystian Fogaça Antunes; Sandra Maria de Mello Cardoso; Rosane Teresinha Fontana; Narciso Vieira Soares; Zaleia Prado de Brum; Francisco Carlos Pinto Rodrigues (Universidade Federal do Paraná, 2016)
This study aimed to investigate, with disabled workers, the main difficulties faced by these in their first months at work. It is qualitative research with 16 disabled workers, in a private company providing teaching services at a high school and higher education level, in the northwest of the Brazilian state of Rio Grande do Sul. Data collection took place through a structured interview and content analysis, in August 2014. It was possible to list two categories: the first, inherent to the difficulties faced by the disabled workers, and the second, to the worker's (dis-)satisfactions and contributions to improving the work process. It was identified that the majority of the interviewees did not face difficulties - however, in some reports, it was possible to learn some instances of discrimination, and difficulties in adapting. Some of the company's actions facilitated the process of the disabled worker's insertion. It is considered that the inclusion of the nurse, within companies, may contribute to the better integration of these workers.